2022
DOI: 10.1097/ta.0000000000003546
|View full text |Cite
|
Sign up to set email alerts
|

Core outcome measures for research in traumatic injury survivors: The National Trauma Research Action Plan modified Delphi consensus study

Abstract: As part of the National Trauma Research Action Plan, we conducted a modified Delphi consensus study to identify and prioritize a set of core outcome domains and measures that will facilitate the synthesis, comparison, and interpretation of long-term trauma outcomes research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 26 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…In 2019, a consensus conference of key stakeholders was convened to propose the optimal metrics to assess long-term outcomes as well as the appropriate instruments with which to measure them 20. Subsequently, the National Trauma Research Action Plan collaborative has proposed 14 patient-reported outcome measures (PROMs) across 13 core domains including activities of daily living, alcohol and substance use, behavioral health metrics (such as PTSD and depression), and measures of general and trauma-specific QoL 21. One substantial concern is that these quantitative metrics, while useful for many surgical conditions may fail to capture the true picture and nuances of outcomes in trauma patients.…”
Section: Data Gathering and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, a consensus conference of key stakeholders was convened to propose the optimal metrics to assess long-term outcomes as well as the appropriate instruments with which to measure them 20. Subsequently, the National Trauma Research Action Plan collaborative has proposed 14 patient-reported outcome measures (PROMs) across 13 core domains including activities of daily living, alcohol and substance use, behavioral health metrics (such as PTSD and depression), and measures of general and trauma-specific QoL 21. One substantial concern is that these quantitative metrics, while useful for many surgical conditions may fail to capture the true picture and nuances of outcomes in trauma patients.…”
Section: Data Gathering and Monitoringmentioning
confidence: 99%
“…20 Subsequently, the National Trauma Research Action Plan collaborative has proposed 14 patientreported outcome measures (PROMs) across 13 core domains including activities of daily living, alcohol and substance use, behavioral health metrics (such as PTSD and depression), and measures of general and trauma-specific QoL. 21 One substantial concern is that these quantitative metrics, while useful for many surgical conditions may fail to capture the true picture and nuances of outcomes in trauma patients. More importantly, they do not provide insight into potential solutions to modulate outcomes.…”
Section: Data Gathering and Monitoringmentioning
confidence: 99%
“…Long term trauma patients outcomes are being increasingly reported within the literature [50], however, the lack of a consistent approach to measuring the outcomes makes comparison and interpretation of the results challenging [50]. A Core Outcome Measurement Set for measuring long term outcomes of trauma patients has recently been developed [51]; however, it lacks input from the families or caregivers of trauma patients.…”
Section: Recommendations For the Futurementioning
confidence: 99%
“…The first used a Delphi technique to identify research gaps across 11 specific areas, including long-term outcomes. The second used a Delphi technique to define optimal metrics to assess long-term outcomes in traumatic injury survivors 15 . Each NTRAP Delphi panel was consisted of subject-matter experts, including researchers from Coalition for National Trauma Research and more than a dozen professional societies.…”
mentioning
confidence: 99%
“…The second used a Delphi technique to define optimal metrics to assess long-term outcomes in traumatic injury survivors. 15 Each NTRAP Delphi panel was consisted of subject-matter experts, including researchers from Coalition for National Trauma Research and more than a dozen professional societies. Across all panels, the NTRAP engaged more than 400 experts.…”
mentioning
confidence: 99%